ANALISIS PROSPEK USAHA TANAMAN HIAS BERDASARKAN KELAYAKAN USAHA DALAM JANGKA WAKTU PROYEK 5 TAHUN PERIODE 2007-2011 - Euis Dasipah; Wardiawan .; N. Yani Novaliana (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2007)
Business of decorative crop represent one of business which is rapidly growing in this time and if elaborated will give a lot of advantage, but the business need the good handling and precisely, the business is also very influenced by trend and consumer appetite hence in conducting this business by the entrepreneur have to earn swiftly fulfill the market request and know any kind of the decorative crop which is trend. This research aim to know what business decorative crop of Flora Sari Nursery in assessment 5 years to the fore fulfill the eligibility of business to be run. The research conducted with the method of case study with the data intake through primary and secondary data. The result of research show the Return Period during 4 years 3 month, Current Net Value with the index 12 % showing number which are positive equal to Rp. 252.908.043, Internal Rate of Return reside index around to 19% - 20% is equal to 19,58 % and make profit index to result number more than one that is 1,27. This result indicate that the business project of Flora Sari Nursery accepted or competent to be run in next 5 years.